Review of Strategies Used in Translating the Taboos of the "Mokhtarnameh" TV Series - Mohadeseh Haddadi; Ali Najafi Ivaki; Mohsen Seifi (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2021)
In all the languages of the world, some words and expressions indicate an unpleasant and impolite concept, which are called "linguistic taboos" or "rhetoric" and are generally avoided from their obvious and direct use. Examination of the "Mokhtarnameh" TV series indicates the use of a significant number of these taboos; In light of this, what is important for the authors of this article is to identify and extract the desired interpretations in the series in the first step, and in the next step, the authors identify techniques used in the translation of this series by a qualitative approach and descriptive-analytical method, evaluate the strengths and weaknesses of the translation by criticizing and examining the inputs of Persian taboos in the Arabic dubbing of the TV series, and present the result to the audience. The result indicates that the translation of the taboos used in the TV series under study can be defined, formatted, and recognized by the most important linguistic strategies in constructing euphemism, including semantic implication, semantic expansion, permissible, omission, reduction, duplication, contradiction, and literal or semantic translations. Another conclusion is that using the method of reduction and contradiction, respectively, has been the most frequent and least frequent strategies in translating the studied TV series.